2017
DOI: 10.1371/journal.pone.0177008
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy of gluteus maximus among women with a history of chronic low back pain

Abstract: BackgroundAlthough the relationship between low back pain (LBP) and the size of certain trunk muscles has been extensively studied, the relationship between gluteus maximus (GM) size and LBP has been only minimally examined. Determining whether such a relationship exists would help improve our understanding of the etiology of LBP, and possibly provide a rationale for the use of therapeutic exercise interventions targeting GM with LBP patients. The objective of this study was to compare gluteus maximus cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 58 publications
2
34
0
1
Order By: Relevance
“…Amabile et al. () reported that the mean normalized gluteus maximus muscle CSA was significantly smaller in female patients with CLBP than in asymptomatic female participants, whereas Kamaz et al. () found no significant difference.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Amabile et al. () reported that the mean normalized gluteus maximus muscle CSA was significantly smaller in female patients with CLBP than in asymptomatic female participants, whereas Kamaz et al. () found no significant difference.…”
Section: Resultsmentioning
confidence: 98%
“…), and the remaining studies were from the USA (Amabile et al. ; Sions et al. ), Poland (Skorupska et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations